Helicobacter pylori Induces Disturbances in Gastric Mucosal Akt Activation through Inducible Nitric Oxide Synthase-Dependent S-Nitrosylation: Effect of Ghrelin. (4th November 2010) - SLomiany, Bronislaw L.; Slomiany, Amalia
Abstract : Gastric mucosal inflammatory response to H. pylori and its key virulence factor, lipopolysaccharide (LPS), are characterized by a massive rise in apoptosis and the disturbances in NO signaling pathways. Here, we report that H. pylori LPS-induced enhancement in the mucosal inducible nitric oxide synthase (iNOS) was associated with the suppression in Akt kinase activity and the impairment in constitutive nitric oxide synthase (cNOS) phosphorylation. Further, we demonstrate that the LPS effect on Akt inactivation, manifested in the kinase protein S-nitrosylation and a decrease in its phosphorylation at Ser 473, was susceptible to suppression by iNOS inhibition. Moreover, the countering effect of hormone, ghrelin, on the LPS-induced changes in Akt activity was reflected in the loss in Akt S-nitrosylation and the increase in its phosphorylation at Ser 473, as well as cNOS activation through phosphorylation. Our findings demonstrate that up-regulation in iNOS with H. pylori infection leads to Akt inactivation through S-nitrosylation that exerts the detrimental effect on the processes of cNOS activation through phosphorylation. We also report that ghrelin protection against H. pylori -induced disturbances is manifested in a marked increase in Akt activity and evoked by a decrease in the kinase S-nitrosylation and the increase in its phosphorylation at Ser 473 .